Resveratrol induces proliferation and differentiation of mouse pre-osteoblast MC3T3-E1 by promoting autophagy - Weiye Cai; Bin Sun; Chao Song; Fei Liu; Zhengliang Wu; Zongchao Liu (BMC, 2023)
Abstract Background In mouse, it was discovered that resveratrol (Res) enhanced osteoporosis (OP) by boosting osteogenesis. Besides, Res can also have an impact on MC3T3-E1 cells, which are crucial for the control of osteogenesis and thus increase osteogenesis. Although some articles have discovered that Res enhanced autophagy to promote the value-added differentiation of MC3T3, it is unclear exactly how this affects the process of osteogenesis in mouse. Therefore, we will show that Res encourages MC3T3-E1 proliferation and differentiation in mouse pre-osteoblasts and further investigate the autophagy-related mechanism for this impact. Methods (1) MC3T3-E1 cells were separated into blank control group and various concentrations (0.01, 0.1, 1, 10, 100µmol/L) of group in order to determine the ideal Res concentration. In the Res group, Cell Counting Kit-8 (CCK-8) was used to measure the proliferation activity of pre-osteoblasts in mice in each group after resveratrol intervention. Alkaline Phosphatase (ALP) and alizarin red staining were used to gauge the degree of osteogenic differentiation, and RT-qPCR was used to measure the expression levels of Runx2 and OCN in the osteogenic differentiation ability of the cells. (2) In the experiment, four groups were set up: the control group, 3MA group, Res group, and Res + 3MA group. To examine cell mineralization, ALP and alizarin red staining were utilized. RT-qPCR and Western blot detection of cell autophagy activity levels and osteogenic differentiation capacity in each group following intervention. Results (1) Resveratrol might increase the number of mice pre-osteoblast, with the impact being most pronounced at 10µmol/L (P < 0.05). The nodules developed substantially more often than in the blank control group, and Runx2 and OCN expressions significantly increased (P < 0.05). (2) In contrast to the Res group, after 3MA purine blocked autophagy, the Res + 3MA group's alkaline phosphatase staining and the development of mineralized nodules were reduced. Runx2, OCN, LC3II / LC3I expression decreased, p62 expression increased (P < 0.05). Conclusion The present study partially or indirectly demonstrated that Res may, through increased autophagy, induce osteogenic differentiation of MC3T3-E1 cells.